1996
DOI: 10.1128/jvi.70.6.3961-3971.1996
|View full text |Cite
|
Sign up to set email alerts
|

cis-Acting signals that promote genome replication in rotavirus mRNA

Abstract: A previous study has shown that rotavirus cores have an associated replicase activity which can direct the synthesis of double-stranded RNA from viral mRNA in a cell-free system (. 68:7030-7039, 1994). To define the cis-acting signals in rotavirus mRNA that are important for RNA replication, gene 8 transcripts which contained internal and terminal deletions and chimeric transcripts which linked gene 8-specific 3-terminal sequences to the ends of nonviral sequences were generated. Analysis of these RNAs in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
61
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 49 publications
7
61
0
Order By: Relevance
“…Similar studies to identify cis-acting signals regulating replication of rotavirus RNA have been carried out using SA11 genome segment 8 (SA11-8) templates (23). These studies also identified a tripartite cis-acting replication signal.…”
Section: Discussionmentioning
confidence: 70%
“…Similar studies to identify cis-acting signals regulating replication of rotavirus RNA have been carried out using SA11 genome segment 8 (SA11-8) templates (23). These studies also identified a tripartite cis-acting replication signal.…”
Section: Discussionmentioning
confidence: 70%
“…These panhandle RNA structures are required for viral RNA transcription and replication (30,51,52). Finally, rotaviruses appear to utilize complementarity at the termini of their viral RNA template to mediate negative-strand RNA synthesis (35,50). Thus, the 5Ј and 3Ј termini of various viral RNA molecules exhibit a predilection for proximal orientations, and these proximal RNA termini seem to facilitate the regulation of viral gene expression and replication.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship between transcription and replication is being understood in greater detail from studies conducted using cystovirus ~6 Van Dijk et al, 1995;Qiao et al, 1997;Mindich, 1999), where a complete viral reconstitution system is available to allow recovery of infectious virions from mRNA transcripts or cDNA clones of the viral genome (Olkkonen et al, 1990). Although no reconstitution system is yet available for any of the reoviruses, studies conducted using baculovirusexpressed recombinant rotavirus-like particles containing the viral RNA polymerase coexpressed with the inner capsid protein have begun to clarify the mechanism by which the dsRNA genome is synthesized from the mRNA templates in rotavirus Patton et al, 1996;Zeng et al, 1996).…”
Section: Mature Mrna Transcriptsmentioning
confidence: 99%